Determination of cross-sectional area of a vessel using impedance technique - Lam, Yu Zhi. (2008)
The cardiac output is a measured parameter that is used to evaluate the overall cardiac condition of critically ill patients and patients with cardiovascular diseases. Presently, there are several techniques for measuring the cardiac output, but these techniques do not allow continuous real-time measurement for both the steady and pulsatile blood flows. An alternative technique is introduced in this thesis which compiles the cardiac output by multiplying the cross-sectional area of a vessel with the velocity of blood flow through the same section of the vessel. The cross-sectional area of the vessel is determined by measuring the impedance of the blood between two or more measuring electrodes placed at the axis of the vessel. Various factors that affect this measurement are taken into consideration, hence thorough investigations of these factors were carried out.